INDONESIAN CAPITAL MARKET REACTION TO THE 2020 US PRESIDENTIAL ELECTION EVENT - Muh. Yunus Kasim; Asngadi; Saranga, Jane Belinda (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This study aims to determine the reaction of the Indonesian Capital Market to the 2020 United States Presidential election. By using the event study method to calculate and analyze differences in Average Abnormal Return (AAR), Average Trading Volume (TVA) and Average Bid-ask Spread (ABAS) during the United States Presidential Election event. The population used is companies listed in the LQ-45 Index with a sample of 39 companies taken with purposive sampling technique. The observation period in this study was 10 working days consisting of 5 days before the event and 5 days after the event. The results found that there were no significant differences in AAR, ATVA and ABAS in the LQ-45 Index. Tests on sectors in the LQ-45 Index show varying results. There are significant ATVA differences in the consumer goods industry sector and in the property, real estate and building construction sector. There are also significant differences in ABAS in the financial, mining and property, real estate and building construction sectors. These results indicate that in some sectors listed in the LQ45 Index, information on the United States Presidential election signals good news to the market in Indonesia so that the market reacts positively around the study period. This study provides implications for investors in making investment decisions, especially during political events.